Analisis Pengaruh Motivasi, Kemampuan Kerja dan Jiwa Wirausaha terhadap Keberhasilan Usaha pada Sentra Kripik Tempe Sanan Malang - Eni Farida; Rahayu Widayanti (Akutansi Bisnis & Manajemen ( ABM ), 2015)
Small and medium industries is part of a national business that has a position and a huge potential in strengthening the structure of the national economy and has a significant role in employment, but on the other hand there are still many problems faced by small industries which are multi dimensions. External issues related to suppliers (suppliers), buyers, competitors, advances in information technology and so on. Internal problems associated with limited human resources (HR, low education levels, lack of motivation, abilities (skills) are also very limited, and low entrepreneurial spirit into its own problems that often result in a business carried on not optimal. Even small industry trends will be less competitive and difficult to develop compared to industries bigger. On the other hand there are many potential that has yet to be optimized. The purpose of this study are: (1) analyze the effect of simultaneously between motivation, ability to work and entrepreneurial spirit to business success, (2) analyze the effect of partially between motivation, ability to work and entrepreneurial spirit to business success, and (3) analyzing the dominant variable affecting the success of the business. This study uses the respondents business owners, primary data collection is done by distributing questionnaires to 79 business owners in the industrial centers. Because the population is less than 100, then the entire population being sampled Chips Tempe Sanan Malang. There are three independent variables were analyzed, namely: motivation, ability to work and entrepreneurial spirit. While the dependent variable is the success of the business. The collected data were then analyzed using multiple linear regression analysis.The analysis showed the presence of simultaneous or partial influence between motivation variables (X1) , the ability to work (X2) and the entrepreneurial spirit (X2) to business success (Y) , indicated by the R2 value of 0.551 or 55.1 %. While that has the most dominant effect is variable entrepreneurial spirit (X3)